Effects of English Language Proficiency (ELP) on the Process of Daily Interpersonal Communication (IPC) between Local and International Students at University Malaysia Pahang (UMP) - Sarwari, Abdul Qahar; Ainol Haryati, Ibrahim; Nor Ashikin, Abdul Aziz (2014)
Interpersonal communication (IPC) is a key factor for students of higher education institutions to gain communicative skills and have enough collaborative activities at the collegiate environment. Therefore, this study was conducted to examine the characteristics of daily IPCs between local and international students of University Malaysia Pahang (UMP). The level of English language proficiency (ELP) and other affecting factors on the process of daily IPCs among participants of this study were evaluated as well. Findings of this study may help lecturers and university officials to design and conduct the essential programs on strengthening of ELP among university students. A triangulation of methods was used to conduct this study by combination of a quantitative survey and the qualitative interviews. The quantitative survey had 220 participants equally from both local and international students of UMP, and also 12 participants were interviewed for the qualitative data as 6 Malaysian and 6 foreigner students. According to the both quantitative and qualitative results, lack of ELP among local and foreigner students of UMP was the main negative affecting factor on the process of their daily interactions among them. Further studies may highlight more aspects of this issue.